Foreign body removal is getting "cooler". Issue 9 (5th July 2016) - Kazachkov, Mikhail; Vicencio, Alfin
Summary: Foreign body removal is commonly performed with the rigid bronchoscope. However, based on recent literature, extraction with the flexible bronchoscope has increased in popularity. Here, we discuss a new tool − the flexible cryoprobe − that may enhance foreign body retrieval in select patients and comment on the methods of foreign body extraction in the view of common clinical practice.Pediatr Pulmonol. 2016; 51:886–888 . © 2016 Wiley Periodicals, Inc.